‘Spiritual But Nor Religious’ – Some Final Reflections - Gemma, Simmonds (New blackfriars, 2016)
In the discourse of a number of theologians there is a perceived gap between spirituality and ‘theology proper’. This gap would not have been perceived or understood by Aquinas, Augustine or others of the long tradition of theological enquiry, since they saw union with God as the highest fruit of theological thinking. There is another gap today between the term ‘spirituality’ used in a loose and decontextualized fashion by the Mind, Body, Spirit industry and those for whom its study is part of mystical theology and its practice part of the church's mystagogia. The fact that many otherwise orthodox believers, as well as those alienated from regular church belief and practice, turn to more esoteric spiritual paths may be a sign that a return to a better-informed and theologically grounded knowledge of the mystical tradition is long overdue.